Photophoretic force on microparticles in complex plasmas - C-R Du; V Nosenko; H M Thomas; A Müller; A M Lipaev; V I Molotkov; V E Fortov; A V Ivlev (New Journal of Physics, 2017)
Experimental observations are presented of unusual (‘abnormal’) microparticles, having trajectories very different from those of the majority of microparticles in the particle cloud in PK-3 Plus chamber (on board the International Space Station). To quantitatively study the mechanism driving this ‘irregular’ motion, we performed a series of experiments with quasi-two-dimensional complex plasmas in a modified GEC RF reference cell in a ground-based laboratory. The results show that the average particle velocity increases with illumination laser power, particularly for the ‘abnormal’ particles. We suggest that the photophoretic force provides an important contribution to the drive, and briefly discuss the mechanism leading to this effect. Optical microscopy results indicate that the ‘abnormal’ particles could be those having deformations or defects on their surface.